Perceived Social Support (PSS) and Work-Life Balance (WLB) in a Developing Country: The Moderating Impact of Work-Life Policy - Uddin, Mahi; Ali, Kalsom Binti; Khan, Mohammad Aktaruzzaman (University of Tehran, College of Farabi, 2024)
Indexed by WOS/Scopus